Rossini Ferreira: características de um choro pernambucano - Alcântara, Reginaldo Salvador de (2008)
The choro can be considered an important Brazilian culture expression, owning general aspects that from in different contexts that happened in the country and especifc characteristics determinated by the singularity in each musical universe. This work shows a especific study about the choro from Pernambuco, it hás the work of the composer Rossini Ferreira as the central focus. From an etnomusicological search from this composer this work hás the general objective show the formal elements that describe the Rossini Ferreira work, manifesting its particularity aesthetic-musical and the social cultural dimension more embracing that from his work. The work was based on a quality search, fundamentally supported in a bibliographical and documental search, that allowed to understand the aspects related to the choro history of Rossini Ferreira, besides were effected a great research work that includes the realization of the interviews, the material sound collecting and the experience of the musical pratice of the Rossini work since the contacts with the misicians straightly related to the composer production. From this search was possible to release characteristics intrinsic to rossiniwork, as well the aspects related to the cultural universe and the choro composer forming. The work evidenced that the choro songs of the composer fit to general elements definers of the stile in Brazil and have significant particularities that give them the singular identity to the other expressions of the genre in the national scenery.